Deposition of indium nitride films by activated reactive evaporation process - a feasibility study - Patil, Sheetal J.; Bodas, Dhananjay S.; Mandale, A. B.; Gangal, S. A. (Applied Surface Science, 2005)
Indium nitride (InN) films are deposited by `activated reactive evaporation (ARE)' process using parallel plate coupled nitrogen plasma (radio frequency source of 13.56 MHz) and evaporation of pure indium powder by resistive heating. Depositions are carried out by varying RF plasma power, on n-type silicon &LANGBRAC; 1 0 0&RANGBRAC; substrate, maintained at room temperature, at a nitrogen gas pressure of 1.06 x 10(-1) Pa (8 x 10 (-4) Torr). The film's crystallinity was examined by X-ray diffraction (XRD) and topography by scanning electron microscope (SEM). The diffraction pattern shows polycrystalline nature of the deposited films with characteristics of hexagonal structure. XRD peak intensity increases with increase in power. SEM observations show a smooth and pinhole free surface having improved quality of film with hexagonal structure as the power is increased from 60 to 120 W. Primary X-ray photoelectron spectroscopy (XPS) results show binding energies of the In 3d levels and N 1s level matching well with that of stoichiometric InN. Further, the refractive index of the films, measured by ellipsometry, is in the range of η = 2.79-2.91 with the variation of plasma power, which is in good agreement with the standard value for indium nitride (η = 2.9). These results indicate the feasibility of using, `activated reactive evaporation (ARE)' process for indium nitride depositions on silicon &LANGBRAC; 1 0 0&RANGBRAC; substrates maintained at room temperature. © 2004 Elsevier B.V. All rights reserved.
Keywords: activated reactive evaporation; ellipsometry; indium nitride; SEM; XRD

Preparation and characterization of a copper based Indian traditional drug: tamra bhasma - Wadekar, M. P.; Rode, C. V.; Bendale, Y. N.; Patil, K. R.; Prabhune, Asmita (Journal of Pharmaceutical and Biomedical Analysis, 2005)
The copper based Indian traditional drug `tamra bhasma' is administered for various ailments since long. Its synthesis involves treating metallic copper with plant juices and then repeated calcination in presence of air so that the metallic state is transformed into the corresponding oxide form traditionally known as `bhasma'. In this work, we present a systematic characterization of this traditional drug using various techniques like X-ray diffraction (XRD), scanning electron microscopy (SEM)-energy dispersive X-ray analysis (EDX), X-ray photoelectron spectroscopy (XPS), infrared spectroscopy (IR), thermogravimetry (TG) and surface area measurement. The results obtained were found to match very well with those of a standard copper oxide confirming the composition of the drug sample. In addition, some specific findings were also made which could help in interpreting the therapeutic properties of the traditional drug `tamra bhasma'. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: copper oxide; crystallite size; tamra bhasma; traditional medicine; XPS of copper oxide; XRD

Studies on characterization of nano CaCO3 prepared by the in situ deposition technique and its application in PP-nano CaCO3 composites - Mishra, Satyendra; Sonawane, S. H.; Singh, R. P. (Journal of Polymer Science Part B: Polymer Physics, 2005)
The elegant approach of in situ deposition technique was used for the synthesis of nano CaCO3 the nanosize of particles was confirmed by the X-ray diffraction (XRD) technique. Differential scanning calorimetry (DSC) was used for determination of the enthalpy. The nano CaCO3 polypropylene (PP) composites were prepared by taking 2 and 10 wt % of different nanosizes (21-39 nm) of CaCO3. Conversion of the alpha phase to beta was observed in the case of 2 wt % of a 30-nm sized amount of CaCO3 in a PP composite. The decrement in DeltaH and percent. crystallinity, as well as the increment in melt temperature were recorded for 6 wt % nano CaCO3 with a decrease in nanosize from 39 to 21 nm. The increment in tensile strength with an increase in the amount of nano CaCO3 was observed, and the tower particle size shoved Greater improvement. The improvement in thermal and mechanical properties is because of the formation of a greater number of small spherulites uniformly present in the PP matrix. (C) 2004 Wiley Periodicals, Inc.
Keywords: Crystallization; DSC; mechanical and thermal properties; nano CaCO3; polypropylene; XRD

Surface disorder in c-Si induced by swift heavy ions - Bogle, Kashinath A.; Gokhale, Suresh P.; Bhoraskar, Vasant N. (Radiation Effects and Defects in Solids, 2005)
The disorders induced in crystalline silicon (c-Si) through the process of electronic energy loss in the swift heavy ion irradiation were investigated. A number of silicon <100> samples were irradiated with 65 MeV oxygen ions at different fluences, 1x10(13) to 1.5x10(14) ions/cm(2), and characterized by the Raman spectroscopy, the optical reflectivity, the X-ray reflectivity, the atomic force microscopy (AFM) and the X-ray diffraction (XRD) techniques. The intensity, redshift, phonon coherence length and asymmetric broadening associated with the Raman peaks reveal that stressed and disordered lattice zones are produced in the surface region of the irradiated silicon. The average crystallite size, obtained by analyzing Raman spectrum with the phonon confinement model, was very large in the virgin silicon but decreased to <100 nm dimension in the ion irradiated silicon. The results of the X-ray reflectivity, AFM and optical reflectivity of 200-700 nm radiation indicate that the roughness of the silicon surface has enhanced substantially after ion irradiation. The diffusion of oxygen in silicon surface during ion irradiation is evident from the oscillation in the X-ray reflectivity spectrum and the sharp decrease in the reflectivity of 200-400 nm radiation. The rise in temperature, estimated from the heat spike model, was high enough to melt the local silicon surface. The results of XRD indicate that lattice defects have been induced and a new plane <211> has been formed in the silicon <100> after ion irradiation. The results of the present study show that the energy deposited in crystalline silicon through the process of electronic energy loss similar to 0.944 keV/nm per ion is sufficient to induce disorders of appreciable magnitude in the silicon surface even at a fluence of similar to 10(13) ions/cm(2).
Keywords: AFM; crystalline silicon; ion irradiation; optical and X-ray reflectivity; Raman; XRD

Synthesis and characterization of microwave-hydrothermally derived Ba1-xSrxTiO3 powders - Deshpande, S. B.; Khollam, Y. B.; Bhoraskar, Y. B.; Date, Sadgopal K.; Sainkara, S. R.; Potdar, H. S. (Materials Letters, 2005)
Submicron-sized, spherical, stoichiometric strontium substituted barium titanate: Ba0.75Sr0.25TiO3 (BST) powders are prepared by microwave-hydrothermal (MH) route under the MH conditions of 200 degreesC, 200 psi, and 30 min in strongly alkaline conditions (pH>12) using potassium titanyl oxalate (KTO) and nitrates of Ba and Sr as the starting precursors and KOH as the mineralizer. The characterization studies by XRD, XRF and SEM indicated that stoichiometric cubic BST powders (a(0)=3.992 A) were obtained by adjusting MH conditions mentioned earlier and keeping the (Ba+Sr)/Ti ratio in starting solution slightly in excess (similar to1.06). (C) 2004 Elsevier B.V. All rights reserved.
Keywords: barium-strontium titanate; dissolution-recrystallization; Microstructure; microwave-hydrothermal synthesis; mineralizer; SEM; XRD; XRF

Synthesis and NMR characterization of SAPO-35 from non-aqueous systems using hexamethyleneimine template - Venkatathri, N (Materials Research Bulletin, 2005)
SAPO-35 was synthesized using hexamethyleneimine template in non-aqueous systems. X-ray diffraction and scanning electron micrograph analysis shows the synthesized sample is pure and well crystalline. Presence of four stages (1.6%, 0.8%, 7.8% and 8.4%) of weight loss is observed by TG/DTA analysis. FT-IR analysis in the framework region shows the presence of tetrahedral T-O-T vibrations is similar to the other known aluminophosphate molecular sieves. FT-IR spectrum in the -OH region shows stretching vibrations at 3631, 3604 and 3580 cm(-1) can be assigned to OH groups in bigger cages near S6R, in bigger cages near D6R and those actually confined inside the D6R, respectively. The spectra for the as-synthesized sample show a single symmetrical Al-27 MAS NMR line at delta = 36.26 indicating the presence of a single tetrahedral aluminium species. Where as Si-29 and P-31 MAS NMR shows the presence of two peaks in both at (-89.9 and -95.15 ppm) and (-34.01 and -40.45 ppm) due to the Si substitution of P present in two different locations in double 6 ring (D6R) and in single 6 ring (S6R). Al-27 3Q-MAS NMR shows two peaks for environmentally different tetrahedral aluminium atoms. This is the first time we are showing such a fact which is not observable using ordinary MAS NMR. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: XRD

Synthesis of high silica content silicoaluminophosphate-5 (SAPO-5) from non-aqueous medium using hexamethyleneimine template - Venkatathri, N (Journal of Scientific & Industrial Research, 2005)
Silicoaluminophosphate-5 (SAPO-5) molecular sieve with up to 2.4 Si atom per unit cell have been synthesized using hexamethyleneimine template in ethylene glycol medium (molar ratio of silica in the reaction gels up to 0.3). Crystallinity and silicon incorporation are confirmed by XRD, XRF, N, sorption study, TG/DTA, SEM. pyridine TPD technique and hydroxyl region FT-IR. These materials with high Si concentration show higher activity for toluene alkylation reaction than samples prepared with up to 0.1 molar ratio of silica in the gel of aqueous media.
Keywords: aqueous; FT-IR; hydroxyl region; non-aqueous; SAPO-5; SEM; TG/DTA; XRD

Direct synthesis of nanocrystalline silver from the reaction between silver carboxylates and n-trioctylphosphine - Charan, Shobhit; Singh, Narendra; Khanna, P. K.; Patil, K. R. (Journal of Nanoscience and Nanotechnology, 2006)
Neat n-Trioctylphosphine (TOP) has been used for the first ever time for reduction of silver nitrate and silver carboxylates (citrate, oleate, and myristate) under mild thermal reaction conditions. UV-visible absorption measurements of re-dispersible silver particles that were obtained by reduction of silver myristrate (product-IV) and silver nitrate (product-I) showed surface plasmon resonance absorption peak at 400 nm. The powder XRD pattern of fcc zero-valent silver resulted in diameters in the range of about 25-30 nm. TEM analysis showed particle diameter similar to that was observed by the XRD. FTIR spectroscopy revealed that the organics from the carboxylate group are retained by the nano-particles in case of product-IV however, presence of TOP is observed in product-I. It is found that when silver nitrate is reduced by TOP, spherical silver nano-particles with poor redispersity are formed but extended heating results in formation of long silver rods of micrometer size however, the re-dispersible nano-particles are easily formed when silver carboxylates are reduced by TOP.
Keywords: Chemical synthesis; Nanocrystalline; noble metal; XRD

Effect of annealing on properties of ZrSe2 thin films - Hankare, P. P.; Asabe, M. R.; Kokate, A. V.; Delekar, S. D.; Sathe, D. J.; Mulla, Imtiaz S.; Chougule, B. K. (Journal of Crystal Growth, 2006)
Thin films of ZrSe2 have been prepared on stainless steel and fluorine-doped tin oxide-coated glass substrates using electrodeposition technique at potentiostatic mode. Double-distilled water containing precursors Zr and Se with ethylene diamine tetra-acetic acid disodium salt as a complexing agent was used to obtain good quality deposits by controlling the rate of reaction. The preparative parameters such as concentration of bath, deposition time, bath temperature, pH of the bath and annealing temperature have been optimized using photoelectrochernical (PEC) technique. The films deposited at optimum preparative parameters are annealed at different temperatures. The film annealed at 200 degrees C shows more photosensitivity. The as-deposited and annealed films at 200 degrees C have been characterized by X-ray diffraction (XRD), energy dispersive analysis by X-ray (EDAX), optical absorption and scanning electron microscopy (SEM). The XRD analysis of the as-deposited and annealed films showed the presence of polycrystalline nature with hexagonal crystal structure. EDAX study reveals that deposited films are almost stoichiometric. Optical absorption study shows the presence of direct transition and band gap energies are found to be 1.5 and 1.38 eV, respectively, for the as-deposited and annealed films. SEM study revels that the grains are uniformly distributed over the surface of substrate for the as-deposited as well as annealed film, which indicates formation of good and compact type of crystal structure. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: band gap; EDAX; Electrodeposition; PEC; SEM; XRD; ZrSe2 thin films

Magnetic properties of NiCuZn ferrites synthesized by oxalate precursor method - Ghodake, S. A.; Ghodake, U. R.; Sawant, S. R.; Suryavanshi, S. S.; Bakare, P. P. (Journal of Magnetism and Magnetic Materials, 2006)
Ni-Cu-Zn ferrites have been synthesized by employing co-precipitation technique using oxalate precursors. X-ray diffractograms did not show impurity phases, indicating single-phase formation of the ferrites. The diffractograms of oxalate complex decomposed at 650 degrees C show that ferritization is complete up to 650 degrees C. Lattice parameter a (angstrom) was found to decrease with the addition of Ni2+ which is attributed to ionic sizes of Ni2+ (0.69 angstrom), which replaces Cu2+ (0.72 angstrom). From the thermogravimetric studies it is observed that the experimentally observed total mass loss (%), agrees with theoretically calculated mass loss (%) indicating maintenance of requisite stoichiometry. Initial permeability (mu(i)) shows increase when Ni2+ is added up to x = 0.15 while for (x > 0. 15), it decreases. The increase in initial permeability (mu(i)) is attributed to monotonic increase in Ms, and K-1 on addition of Ni2+. However, the microstructure and density (porosity) also influence mu(i) variations. The decrease in pi is attributable to increase of K-1. The composition with density 91.14% exhibits large mu(i) which also tends to increase with temperature up to 60 degrees C. Thus its usable range extends up to 60 degrees C. This samples has T-c near to 160 degrees C. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: initial permeability; magneticproperties; Magnetization; NiCuZn ferrites; XRD

Radiation assisted synthesis of nanosized barium zirconate - Athawale, Anjali A.; Chandwadkar, Asha J.; Karandikar, Prashant R.; Pasricha, R.; Bapat, Malini S. (Radiation Physics and Chemistry, 2006)
This paper reports the synthesis of refractory barium zirconate using solid-state reactive precursors subjected to gamma-radiations of a Co-60 source. Influence of varying doses on the formation of cubic phase of BaZrO3 has been investigated with the stepwise analysis of the intermediate products by means of FT-IR, XRD and TGA techniques. TEM depicts the nanospherical nature of the BaZrO3 particles. (C) 2006 Elsevier Ltd. All rights reserved.
Keywords: Ceramics; gamma-radiation; Nanoparticles; perovskite; refractory; XRD

Synthesis and characterization of high silica content silicoaluminophosphate SAPO-35 from non-aqueous medium - Venkatathri, N. (Catalysis Communications, 2006)
SAPO-35 with up to 15.6 Si atoms per unit cell have been synthesized, using hexamethyleneimine as template in ethylene glycol medium (molar ratio of silica in the reaction gets up to 2.5). Crystallinity and silicon incorporation was confirmed by XRD, XRF, TG/DTA, SEM, FT-IR and Al-27 and Si-29 MASNMR. These SAPO-35 materials with high Si concentration show higher activity for methanol to olefin reaction than samples prepared with up to 0.3 molar ratio of silica in the get. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: ammonia adsorption; FT-IR; MASNMR; methanol to olefin; non-aqueous medium; SAPO-35; SEM; TG/DTA; XRD

Synthesis and characterization of TAPO-31 molecular sieves using tripropylamine template - Venkatathri, N.; Shetty, V. N. (Catalysis Communications, 2006)
TAPO-31 was synthesized hydrothermally using a novel template tri-n-propylamine for the first time. C and N analysis shows the butanol from titanium tetrabutoxide plays an important role in the synthesis. The incorporation of titanium into framework of phosphorous and both aluminiurn and phosphorous sites was suggested from elemental analysis. Isomorphous substitution of titanium (III) in AlPO framework was confirmed from ESR and (31)p MASNMR spectra. UV-Vis and XPS spectra revealed a partial oxidation of framework titanium (III) into titanium (IV) in the calcined TAPO-31 and thus the presence of redox centers in the products. The higher titanium content (Al/Ti = 10) TAPO-31 sample shows higher activity for phenol hydroxylation compared to lower titanium content (Al/Ti = 20) and Titanium impregnated AIPO(4)-31. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: ESR; FT-IR; MASNMR; SEM; TAPO-31; TG/DTA; tripropylamine; UV-Vis; XPS; XRD

Synthesis, characterization and catalytic properties of vanadium aluminophosphate molecular sieves VAPO-31 and VAPSO-Amr from non-aqueous media - Venkatathri, N. (Applied Catalysis A-General, 2006)
Vanadium samples containing aluminophosphate molecular sieve (VAPO-31) and amorphous vanadium silicoaluminophosphate (VAPSO-Amr) have been synthesized using hexamethyleneimine template from non-aqueous media for the first time. XRD and SEM analyses confirm the phase purity of the synthesized samples. FT-IR analysis suggests the incorporation of V4+ in the aluminophosphate framework. ESR, UV-vis spectroscopic, and XPS techniques and cyclicvoltametric studies confirm the incorporation of vanadium and reveal its presence in tetrahedral and square pyramidal environments in the as-synthesized samples. Cyclic voltammetry reveals the presence of two redox couples in VAPO-31. This catalyst is found to be a good oxidation catalyst. Although most of the properties of VAPO-31NA and VAPSO-Amr are similar, the latter can access more vanadium and V4+ ions. Compared to aqueous media samples, it can incorporate more vanadium especially V5+, ions and has been found to be better oxidation catalyst. The physicochemical properties also change with media. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: cyclic voltammetry; ESR; FT-IR; MAS NMR; non-aqueous; SEM; TG/DTA; UV-Vis; VAPO-31; XPS; XRD

Synthesis of cadmium selenide thin films at low-temperature by simple chemical route and their characterization - Hankare, P. P.; Delekar, S. D.; Asabe, M. R.; Chate, P. A.; Bhuse, V. M.; Khomane, A. S.; Garadkar, K. M.; Sarwade, B. D. (Journal of Physics and Chemistry of Solids, 2006)
Crystalline CdSe thin film has been deposited using appropriate precursor solution containing cadmium sulfate octahydrate, tartaric acid, potassium hydroxide, ammonia and sodium selenosulfate. The effect of parameters such as bath composition, deposition temperature, pH of the solution, speed of the rotation and the specificity of complexing agent on growth process is studied. The `as-deposited' CdSe thin film was found to be red in color, specularly reflective and well adherent to the glass substrate. The crystalline phase of the deposited sample was hexagonal wurtzite-type. The analysis of optical absorption data shows energy band gap energy (E-g) 2.01 eV. The morphological study and compositional analysis of film sample have been discussed. The electrical resistivity of CdSe thin film was found to the order of 10(6) Omega cm. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: XRD

Unusual formation of nano-particles of CdO and Cd(OH)(2) from the reaction of dimethyl cadmium with DMF - Singh, Narendra; Charan, Shobhit; Patil, K. R.; Viswanath, A. K.; Khanna, P. K. (Materials Letters, 2006)
This paper presents generation of CdO and Cd(OH)(2) nano-particles from Dimethyl Cadmium in DMF. The CdO nano-particles were obtained instead of CdSe, even when the reaction was done in presence of 1,2,3-selenadiazole (the source of selenium) with Me2Cd in DMF (product-I). The direct reaction of Me2Cd in DMF also leads to formation of CdO (product-II). However, Cd(OH)(2) nano-particles were obtained when Me2Cd was refluxed in DMF for a few hours followed by reaction of H2S gas (product-III). The formation of Cd(OH)(2) was also established via decomposition Of Me2Cd:Et2O adduct (product-IV). Nano-particles of CdO and Cd(OH)(2) (product-I to product-IV) were characterized by X-ray powder diffraction (XRD), TEM and SEM/EDS measurements, FTIR, thermal analysis (TGA) and XPS analysis. The particle size of all the products as calculated by XRD patterns were in the range of about 20 nm. TEM images showed that the products are agglomerated clusters with the particles in the nano-meter regime. The synthesis however, is understood to be unusual as the reactions with selenium source and sulfur source should have generated the CdSe and CdS however, the end products were always found to be the product-I to product-IV (c) 2006 Elsevier B.V. All rights reserved.
Keywords: Chemical synthesis; Nanoparticles; Semiconductor; XRD

Synthesis and MASNMR characterization of VPI-5 molecular sieve - Venkatathri, N. (Asian Journal of Chemsitry, 2007)
The synthesized VPI-5 sample was characterized by XRD, SEM, FTIR, TG/DTA, Al-27, P-31 and 3Q MASNMR techniques, which shows that the sample was highly crystalline. Carbon and nitrogen analysis reveals that the sample contains no template molecules; however, TG/DTA analysis shows the presence of physisorbed template molecules. MASNMR results show the presence of two different types of aluminium and phosphorus, 3Q MASNMR shows the presence of two types of environmentally different tetrahedral aluminium, which are not observable by ordinary MASNMR along with known octahedral aluminium.
Keywords: 3Q-MASNMR; FTIR; MASNMR; SEM; synthesis; TG/DTA; VPI-5; XRD

Bacterial synthesis of copper/copper oxide nanoparticles - Hasan, Syed Saif; Singh, Sanjay; Parikh, Rasesh Y.; Dharne, Mahesh S.; Patole, Milind S.; Bhagavatula L. V. Prasad; Shouche, Yogesh S. (Journal of Nanoscience and Nanotechnology, 2008)
A bacterial mediated synthesis of copper/copper oxide nanoparticle composite is reported. A Gram-negative bacterium belonging to the genus Serratia was isolated from the midgut of Stibara sp., an insect of the Cerambycidae family of beetles found in the Northwestern Ghats of India. This is a unique bacterium that is quite specific for the synthesis of copper oxide nanoparticles as several other strains isolated from the same insect and common Indian mosquitoes did not result in nanoparticle formation. By following the reaction systematically, we could delineate that the nanoparticle formation occurs intracellularly. However, the process results in the killing of bacterial cells. Subsequently the nanoparticles leak out as the cell wall disintegrates. The nanoparticles formed are thoroughly characterized by UV-Vis, TEM, XRD, XPS and FTIR studies.
Keywords: bacterial synthesis; Nanoparticles; TEM; XPS; XRD

Co-precipitation method for preparation of Bi3TiNbO9 powders - Gupta, U. N.; Samuel, V.; Muthurajan, H.; Kumar, H. H.; Patil, S. D.; Ravi, V. (Ceramics International, 2008)
A simple co-precipitation technique has been successfully used for the preparation of pure, ultrafine, single phase Bi3TiNbO9 (BTN). An aqueous ammonium hydroxide solution was used to simultaneously precipitate Bi3+, Ti4+ and Nb5+, cations as hydroxides under basic conditions (pH similar to 9). No pyrochlore phase was found while heating powder at 500 degrees C and pure BTN phase was found to be formed by X-ray diffraction (XRD). For comparison, BTN samples were also synthesized by the traditional solid state method. The sequence of phase formation in both cases were investigated by XRD studies. (c) 2007 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Ceramics; Chemical synthesis; electronic material; Oxides; XRD

Phosphotungstic acid on silica with modified acid sites as a solid catalyst for selective cleavage of tert-butyldimethylsilyl ethers - Bhure, Mahesh H.; Kumar, Indresh; Natu, Arun D.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (Catalysis Communications, 2008)
The strength and nature of acid sites of bulk phosphotungstic acid could be modified after dispersing it on silica support which was characterized by XRD, ammonia TPD and (31)P MAS NMR techniques. This solid acid catalyst was found to be highly selective for the cleavage of tert-butyldimethylsilyl ethers at room temperature. The catalyst was easily recovered by filtration and could be reused for several times without loss of any activity giving a TON of 9.5 x 10(5). (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Ammonia TPD; Catalytic cleavage; reaction pathway; solid acid; tert-butyldimethylsilyl ethers; XRD

Reaction kinetics of liquid phase air oxidation of p-cresol to p-hydroxybenzaldehyde - Kshirsagar, V. S.; Nadgeri, J. M.; Tayade, P. R.; Rode, C. V. (Applied Catalysis A-General, 2008)
The kinetics of liquid phase oxidation of p-cresol to p-hydroxybenzaldehyde has been investigated using insoluble cobalt oxide (CO3O4) catalyst at oxygen partial pressures in the range 0.1-1.5 MPa, reaction temperatures 333-393 K, p-cresol concentrations 0.49-1.53 kmol/m(3) and catalyst loadings 0.38-3.03 kg/m(3). The effects of oxygen partial pressure, reaction temperature, p-cresol concentration and catalyst loading on the initial rate of reaction have been studied. The initial rate varied linearly with catalyst loading up to 1.5 kg/m(3) beyond which it was independent of the catalyst loading while first-order dependence was observed with variation in oxygen partial pressure. A rate expression has been proposed considering Langmuir-Hinshelwood (LH) type mechanism, based on the initial rate data. A batch reactor model was also developed based on the kinetics studied and the concentration time profile predicted by the model was in good agreement with the experimental data. The activation energy for the liquid phase oxidation of p-cresol was found to be 39.6 kJ/mol. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Co3O4; kinetics; p-cresol oxidation; XPS; XRD

Synthesis of bismuth titanate (Bi4Ti3O12)powders via calcination of microwave-hydrothermally (MH) derived precursor - Khollam, Y. B.; Deshpande, S. B.; Samuel, V.; Potdar, H. S. (Indian Journal of Engineering and Materials Sciences, 2008)
Micrometer sized platelet-like particles of bismuth titanate (Bi4Ti3O12) ire prepared successfully by the calcination of a mixed-precursor in air. The mixed precursor is precipitated Under microwave-hydrothermal (MH) treatment via dissolution-recrystallization kinetics. The mixed precursor is precipitated in-situ by giving MH treatment (at 200 degrees C, 200 psi, and 30 min hold time) to the hydrolysed slurry containing Bi and Ti cations. The slurry was prepared by adding 20% aqueous KOH precipitant solution to a well-mixed stoichiometric nitrate solution containing Bi and Ti cations. XRD results revealed that the as-dried precursor consisted of a homogenous mixture of non-crystalline particles of Bi2O3 and TiO2. The calcination of the as-dried precursor at 700 degrees C/2 h in air resulted ill the formation of micron sized platelet like single-phase Bi4Ti3O12 powders having orthorhombic structure.
Keywords: Bi4Ti3O12; MH processing; SEM; XRD

Catalytic activity of cobalt containing MCM-41 and HMS in liquid phase oxidation of diphenylmethane - Bhoware, Shrikant S.; Kamble, K. R.; Singh, A. P. (Catalysis Letters, 2009)
Cobalt containing MCM-41 and HMS were synthesized by direct hydrothermal (DHT) and post synthesis methods (grafting and immobilization). The catalytic activity of these materials was investigated in the liquid phase oxidation of diphenylmethane at 80 A degrees C with TBHP (70 wt%) as oxidant. Comparative study of cobalt containing MCM-41 and HMS was carried out to reveal the catalytic performance of framework, extraframework and immobilized cobalt species. The role of the solvent in the performance of catalyst was examined with different polar and non polar solvents. Oxidation of diphenylmethane in solvent free media (under similar reaction conditions) shows formation of hydroxy derivatives of benzophenone in addition to main product (benzophenone). Hundred percent selectivity to benzophenone was obtained when the reaction was carried out in solvent.
Keywords: diphenylmethane; HMS; Immobilization; MCM-41; XRD

Growth of barium oxalate crystals in agar-agar gel and their characterization - Dalai, P. V.; Saraf, K. B.; Shah, S. (Crystal Research and Technology, 2009)
{Single crystals of barium oxalate have been grown by get method using agar-agar gel as media of growth at ambient temperature. The optimum conditions were established by varying various parameters such as concentration of gel, concentration of reactant, gel setting time etc. Prismatic platy shaped transparent crystals were obtained. The grown crystals were characterized through powder X-ray diffraction (XRD), Fourier transform infrared (FT-IR) studies, Thermogravimetric (TGA) and Differential thermal analysis (DTA). The compound crystallizes under monoclinic structure with lattice parameters a = 6.6562 angstrom
Keywords: barium oxalate; Crystal growth; FT-IR; TGA/DTA; XRD

Solid state synthesis and room temperature magnetic properties of iron phosphide nanoparticles - Singh, N.; Khanna, P. K.; Joy, Pattayil Alias (Journal of Nanoparticle Research, 2009)
Room temperature magnetic properties have been achieved for nano-crystalline iron phosphide synthesized from the direct solid state reaction of iron chloride and tri-octylphosphine (TOP). The magnetization continuously increased with higher magnetic fields, indicating a super-paramagnetic behavior. It is observed that room temperature magnetism is possible for the material showing antiferromagnetic nature at low temperatures. In the present synthesis, TOP acted as a source of phosphorus as well as a surfactant. X-ray diffraction (XRD) studies revealed that the black powder is a mixture of FeP and Fe(2)P. Transmission electron microscopy (TEM) and scanning electron microscopy (SEM) showed elongated as well spherical particles. Energy dispersion X-ray analysis (EDAX) confirmed a non-stoichiometric iron phosphide. Presence of TOP was confirmed by infra-red (IR) spectroscopy, and thermo-gravimetric analysis (TGA) indicated about 6% wt. loss due to presence of organics.
Keywords: Iron phosphide; Semiconductors; Solid state reaction; synthesis; XRD

Highly sensitive and fast responding CO sensor based on Co3O4 nanorods - Patil, Dewyani; Patil, Pradip; Subramanian, Vijayanand; Joy, Pattayil Alias; Potdar, Hari S. (Talanta, 2010)
Co3O4 nanorods (diameters similar to 6-8 nm and lengths similar to 20-30 nm) were synthesized for the first time through a simple co-precipitation/digestion method by calcination of cobalt hydroxyl carbonate in air and their CO gas sensing properties were investigated. The Co3O4 nanorods exhibited outstanding gas sensing characteristics such as, higher gas response (similar to 6.55-50 ppm CO gas at 250 degrees C), extremely rapid response (similar to 3-4s), fast recovery (similar to 5-6s), excellent repeatability, good selectivity and lower operating temperature (similar to 250 degrees C). Furthermore, the Co3O4 nanorods are able to detect up to 5 ppm for CO with reasonable sensitivity (similar to 3.32) at an operating temperature 250 degrees C and they can be reliably used to monitor the concentration of CO over the range (5-50 ppm). The experimental results clearly demonstrate the potential of using the Co3O4 nanorods as sensing material in the fabrication of CO sensors. Plausible CO sensing mechanism of the Co3O4 nanorods is also discussed. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: CO sensor; Co3O4 nanorods; HRTEM; Semiconductor gas sensors; XPS; XRD

Synthesis and characterization of novel aromatic-aliphatic polyamides from bis-[(4-aminobenzyl)-4-benzamide] ether - Patil, A. S.; Medhi, M.; Sadavarte, Nilakshi V.; Wadgaonkar, P. P.; Maldar, Noormahamad N. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2010)
A novel aromatic diamine monomer containing preformed aromatic-aliphatic amide and ether linkage, bis-[(4-aminobenzyl)-4-benzamide] ether (BABE) was prepared from 2-phenylacetonitrile. BABE was characterized by FT-IR, (1)H NMR, (13)C NMR and mass spectrometry. Five new aromatic polyamides were prepared by low temperature solution polymerization from BABE and different mole proportions of isophthaloyl chloride (IPC) or terephthaloyl chloride (TPC). The resulting polymers were characterized by means of FT-IR, inherent viscosity [eta(inh)], solubility, differential scanning calorimetry [DSC], thermogravimetric analysis [TGA] and X-ray diffraction [XRD]. Polyamides were obtained in good yields and had moderate to high molecular weights as indicated by inherent viscosities in the range 0.63-1.35 dL/g in (DMAc + 4% LiCl). XRD results showed the partly crystalline nature of polymers and these polymers dissolved in aprotic polar solvents containing LiCl. The solubility of copolyamides improved due to random placement of constituent IPC and TPC during polymerization. DSC analysis of these polyamides showed glass transition temperatures in the range of 197-204 degrees C, and they showed no weight loss below 336 degrees C when analyzed by TG. These polyamides have potential applications as engineering materials. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Bis-[(4-aminobenzyl)-4-benzamide] ether; ether linkage; Inherent viscosity; polyamides; thermal stability; XRD

Glycerol mediated low temperature synthesis of nickel nanoparticles by solution reduction method - Singh, Kalpana; Kate, Kunal H.; Chilukuri, V. V. Satayanarayana; Khanna, P. K. (Journal of Nanoscience and Nanotechnology, 2011)
Phase pure Nickel nano-particles were synthesized by in-situ generation of nickel hydrazine hydrate complex (Ni-HH) followed by its decomposition in an alkaline glycerol medium. The synthesis can be performed in an open beaker with or without the use of surface protective reagents. By using the present method, Ni nano-particles can be prepared in large scale. The black nano-powders so-obtained were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), selected area electron diffraction (SAED), Scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), Fourier transform infra-red (FTIR) spectroscopy and thermal analysis (TGA). XRD and SAED analysis revealed that the synthesized particles were pure crystalline nickel with FCC structure.
Keywords: Chemical Reduction; Nano-Particles; synthesis; Transition Metal; XRD

Highly sensitive and selective LPG sensor based on alpha-Fe2O3 nanorods - Patil, Dewyani; Patil, Virendra; Patil, Pradip (Sensors and Actuators B-Chemical, 2011)
The alpha-Fe2O3 nanorods were successfully synthesized without any templates by calcining the alpha-FeOOH precursor in air at 300 degrees C for 2 h and their LPG sensing characteristics were investigated. The alpha-FeOOH precursor was prepared through a simple and low cost wet chemical route at low temperature (40 degrees C) using FeSO4 center dot 7H(2)O and CH3COONa as starting materials. The formation of alpha-FeOOH precursor and its topotactic transformation to alpha-Fe2O3 upon calcination was confirmed by X-ray diffraction measurement (XRD). X-ray photoelectron spectroscopy (XPS), field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) analysis. The alpha-Fe2O3 nanorods exhibited outstanding gas sensing characteristics such as, higher gas response (similar to 1746-50 ppm LPG at 300 degrees C), extremely rapid response (similar to 3-4 s), relatively slow recovery (similar to 8-9 min), excellent repeatability, good selectivity and lower operating temperature (similar to 300 degrees C). Furthermore, the alpha-Fe2O3 nanorods are able to detect up to 5 ppm for LPG with reasonable response (similar to 15) at the operating temperature of 300 degrees C and they can be reliably used to monitor the concentration of LPG over the range (5-60 ppm). The experimental results clearly demonstrate the potential of using the alpha-Fe2O3 nanorods as sensing material in the fabrication of LPG sensors. Plausible LP G sensing mechanism of the alpha-Fe2O3 nanorods is also discussed. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: alpha-Fe2O3 nanorods; FESEM; LPG sensor; Semiconductor gas sensors; TEM; XPS; XRD

Polyamides containing quinoxaline moiety - Patil, Vidyadhar B.; Sayyed, Maheboob M.; Mahanwar, Prakash A.; Wadgaonkar, Prakash P.; Maldar, Noormahamad N. (Journal of Polymer Research, 2011)
A new quinoxaline moiety containing aromatic diamine; 2,3-bis[4-(4-aminophenoxy)phenyl]quinoxaline (APQ) was synthesized starting from 4-methoxybenzaldehyde and was characterized by IR, (1)H, (13)C NMR and Mass spectrometry. Five new polyamides were synthesized by polycondensation of various aliphatic diacid / aromatic diacids namely, azelaic acid, bis(4-carboxyphenyl)dimethylsilane, 4,4'-oxybis(benzoicacid), isophthalic acid and terephthalic acid with APQ by Yamazaki's phosphorylation method using triphenyl phosphite as condensing agent. The polyamides were characterized by IR spectroscopy, solubility tests, inherent viscosity, X-ray diffraction technique, differential scanning colorimetry and thermogravimetric analysis. The polyamides had inherent viscosities in the range 0.39-0.45 dL/g in N, N-dimethylacetamide at 30 +/- 0.1 A degrees C. The polyamides were soluble in polar aprotic solvents such as N, N-dimethylacetamide, N, N-dimethylformamide, dimethylsulfoxide, N-methylpyrrolidone. X-Ray diffraction studies showed that polyamides were amorphous in nature. The polyamides showed glass transition temperatures in the range 104-205 A degrees C, according to differential scanning calorimetry. Thermogravimetric analysis exhibited initial decomposition temperatures above 348 A degrees C; indicating that these polyamides possessed excellent thermal stability.
Keywords: polyamides; Quinoxaline; solubility; Thermal properties; XRD

Sodium-doped lithium zirconate nano squares: synthesis, characterization and applications for CO2 sequestration - Khokhani, Mrinal; Khomane, Ramdas B.; Kulkarni, Bhaskar D. (Journal of Sol-Gel Science and Technology, 2012)
Nano squares of sodium-doped lithium zirconate have been synthesized by a simple citrate based sol-gel method at room temperature in the presence of cetyl trimethylammonium bromide (CTAB) as a surfactant. The structural and morphological properties were investigated by X-ray diffraction (XRD) and Transmission Electron Microscopy (TEM) respectively. XRD analysis of sample calcined at 900 A degrees C for 4 h shows the formation of monoclinic lithium zirconate phase. The TEM shows the interesting morphology of formation of nano squares of sodium doped lithium zirconate sample. The carbon dioxide sorption capacity was carried out by TGA analysis at different high temperatures. It is observed that the sample shows similar to 20 wt% carbon dioxide sorption at higher temperature (650 A degrees C) within 20 min which are better than the known reports.
Keywords: Carbon dioxide; CTAB; Lithium zirconate; Sodium doped lithium zirconate; sol-gel; TEM; XRD

Resistance to ionic pt insertion in oxygen excess LaMnO3 perovskite lattices and its effect in water gas shift reaction - Rajesh, Thattarathody; Devi, R. Nandini (Journal of Molecular Catalysis A-Chemical, 2014)
Pt doped and impregnated LaMnO3 perovskites are synthesized at different temperatures and Pt and Mn states are compared in an attempt to get insight into extent of lattice incorporation of Pt in perovskite. Various characterization studies indicate that oxygen excess system like LaMnO3 presents substantial resistance to B site doping with Pt. This behavior is different from other oxygen deficient perovskites like LaCoO3 and LaFeO3 in which lattice incorporation stabilizes the active species against sintering. Water gas shift reaction was used as a probe reaction to understand the effect of this difference in the activity. In case of LaMnO3, failure in lattice substitution leads to sintering and deactivation at high synthesis temperatures (>= 700 degrees C) in both impregnated and doped samples. In doped samples, however, a strong interaction of Pt species with a persistent amorphous phase prevents sintering at lower synthesis temperature thereby enhancing the activity when compared to impregnated sample. The study reveals a possible mechanism in which only Pt(0) species is active with perovskite playing a minimal role in this system due to the resistance to lattice incorporation. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Oxygen excess; Perovskites; Water gas shift reaction; XPS; XRD

Preparation and characterization of flexible ferromagnetic nanocomposites for microwave applications - Thomas, Teena; Kanoth, Bipinbal P.; Nijas, C. M.; Joy, Pattayil Alias; Joseph, Joseph M.; Kuthirummal, Narayanan; Thachil, Eby T. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2015)
Magnetic Fe3O4 nanoparticles (similar to 20 nm) were synthesized using the chemical co-precipitation method with a view of developing flexible and easily processable ferromagnetic materials with high mouldability to be used as microwave absorbers. The nanoparticles prepared were incorporated into natural rubber through latex stage processing. This novel processing method gives better dispersion of particles in the rubber matrix. The composites were characterized using XRD, SEM, vibrating sample magnetometer, dynamic mechanical analyzer, cavity perturbation, thermogravimetry (TGA), and Fourier transform infrared photoacoustic spectroscopy (FTIR-PAS). A notable improvement in the mechanical properties of composites was observed upon adding Fe3O4 particles. Magnetic and microwave characteristics of the composites indicate the formation of a flexible ferromagnetic material with good microwave absorption characteristics. (C) 2015 Published by Elsevier B.V.
Keywords: Fe3O4; Ferromagnetic; FTIR-PAS; Microwave absorption; Natural rubber; SEM; XRD

Photocatalytic H-2 evolution from water-methanol mixtures on InGaO3(ZnO)(m) with an anisotropic layered structure modified with CuO and NiO cocatalysts - Narendranath, Soumya B.; Thekkeparambil, Saranya V.; George, Leena; Thundiyil, Shibin; Devi, R. Nandini (Journal of Molecular Catalysis A-Chemical, 2016)
InGaO3(ZnO)(m) series of oxides is found to be active for photocatalytic H-2 evolution from water-methanol mixtures. The structure of this series is highly anisotropic with InO6 octahedral layers sandwiching Ga/ZnOn polyhedra. The structural anisotropy in which the conducting layer is spatially separated from the charge generation sites may help in suppressing charge recombination and consequently enhance catalytic activity. The band gaps of the series obtained from absorption spectra are above 3.6 eV and hence they are not active under visible light irradiation. H-2 evolution is considerably enhanced under UV light on employing NiO as cocatalyst due to facile electron transfer from InGaO3(ZnO)(m). to NiO. However, when CuO is used as cocatalyst, visible light activity could be brought out. Due to the very low band gap of CuO, it can act as a sensitizer absorbing in visible light. The band positions become conducive for H-2 evolution due to band alignments consequent to electron accumulation in CuO conduction band. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: InGaO3(ZnO)(m); photocatalytic water splitting; visible light; XPS; XRD

Solubility limits of ceria-zirconia-lanthana solid-solutions - Abbas, Zenab; Surendran, Mythili; Anjana, P. A.; Jidev, P. K.; Dasari, Harshini; Naidu, Sudhakar N.; Anandhan, S.; Bhat, Udaya K.; Babu, Uday Bhaskar G.; Dasari, Hari Prasad (International Conference on Recent Trends in Engineering and Material Sciences (ICEMS), 2017)
We demonstrate, the solubility limits of Ceria-Zirconia-Lanthana (CZLa) solid-solutions with the increase in heat-treatment temperature from 600 degrees C to 1300 degrees C. CZLa nano-crystalline samples were successfully synthesized by EDTA-Citrate complex method and were characterized by Raman Spectroscopy (RS) and Transmission Electron Microscopy (TEM) analysis. With an increase in temperature, it is noticed that the solubility limit is decreased in CZLa system. At 600 degrees C, a very good solubility is observed in CZLa system and is confirmed from RS analysis. At higher heat-treatment temperatures (1000 and 1300 degrees C), with an increase in La content, Zr precipitated in the CZLa system and is confirmed from RS analysis. The reason for such kind of behavior in this CZLa system is clearly explained in this work. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Ceria-Zirconia Lanthana; EDTA-Citrate method; Raman spectroscopy; solubility limit; XRD

Solvothermal growth of PbBi2Se4 nano-flowers: a material for humidity sensor and photodetector applications - Aher, Rahul; Bhorde, Ajinkya; Nair, Shruthi; Borate, Haribhau; Pandharkar, Subhash; Naik, Dhirsing; Vairale, Priti; Karpe, Smita; Late, Dattatray; Prasad, Mohit; Jadkar, Sandesh (Physica Status Solidi A-Applications and Materials Science, 2019)
In the present work, lead bismuth selenide (PbBi2Se4) nano-flowers are synthesized by using a simple solvothermal method. Humidity sensor and photodetector based on PbBi2Se4 nano-flowers are fabricated on indium tin oxide (ITO) substrates and their sensing properties are investigated. Formation of PbBi2Se4 is confirmed by XRD, EDS, and XPS whereas formation of nano-flowers is confirmed by SEM and TEM analysis. XRD analysis reveals the hexagonal crystal structure of PbBi2Se4 phase with a = b = 4.22 angstrom, and c= 17.42 angstrom. The surface morphology of PbBi2Se4 clearly shows the formation of well-organized flower-like nanostructures which closely resembles the shape of Dahlia. The elemental mapping of chemical constituents obtained from SEM-EDS analysis shows uniform distribution of chemical constituents for the Pb, Bi, and Se in PbBi2Se4 nano-flowers. The PbBi2Se4 nano-flowers based humidity sensor has a typical response time of approximate to 65s and recovery time of approximate to 75 s. In case of PbBi2Se4 nano-flowers-based photodetector, the response and recovery time are observed approximate to 121 and approximate to 123 s, respectively, under visible light illumination with photoresponsivity (5 x 10(-6)), photosensitivity (2.16%), and quantum efficiency (1.5 x 10(4)). The obtained results demonstrate the potential applications of solvothermally grown PbBi2Se4 nano-flowers-based devices for humidity sensors and photodetectors. The ease of the present work is to develop novel material to obtain device quality humidity sensors and photodetectors.
Keywords: humidity sensor; PbBi2Se4; photodetector; XPS; XRD

Influence of cobalt on performance of Cu-CeO2 catalysts for preferential oxidation of CO - Malwadkar, Sachin; Bera, Parthasarathi; Satyanarayana, C. V. V. (Journal of Rare Earths, 2020)
{Copper and cobalt oxides supported on CeO2 were investigated for preferential oxidation of carbon monoxide (CO-PROX) in the presence of excess hydrogen and CO2. (CuO)(1-x)(Co3O4)(x/3)-(CeO2)(2.5) (x = 0, 0.25, 0.50, 0.75, 0.85 and 1) catalysts were prepared by coprecipitation method. These mixed oxide catalysts were characterized by several physicochemical techniques, such as BET surface area (SBET), X-ray diffraction (XRD), high resolution transmission electron microscopy (HRTEM), temperature programmed reduction (TPR) and X-ray photoelectron spectroscopy (XPS). XRD studies show the peaks related to CuO and Co3O4 phases in copper and cobalt containing CeO2 catalysts. The average particle size of the CeO2 crystallites is in the range of 8-10 nm as evaluated from HRTEM studies. XPS studies demonstrate that Cu, Co and Ce in (CuO)(1-x)(Co3O4)(x/3)-(CeO2)(2.5) catalysts are presented in +2 and +1, +3 and +2 and +4 and +3 oxidation states, respectively. The catalyst with x = 0.75 shows better activity and selectivity towards CO-PROX. Though the catalyst with only copper (CuO-CeO2
Keywords: CO-PROX; Cu-CeO2; H2O addition; Methanation; XPS; XRD